Wrist drop as presentation of ischemic stroke: A case report - Karacan, Meltem; Ilik, Faik; Gönen, Murat (Turkish Society of Cerebrovascular Diseases, 2016)
Focal hand weakness is a rare condition in cerebrovascular diseases which is presented focal neurological deficit. Often misdiagnosed in favor of peripheral lesion. Radial nerve is responsible for extension the wrist, and controls portion of the hand. Paralysis of radial nerve causes weakness of the wrist and fingers, also called wrist drop. In our study we presented a case, which has wrist drop due to cerebrovascular disease. Copyright © 2012 TBDHD.
Düşük el ile prezente olan iskemik inme: Bir vaka sunumu
Keywords: Ischemic stroke; Posterior interosseous nerve.; Radial neuropathy; Wrist drop